A Fast and Reliable Tree based Proactive Source Routing in Mobile Adhoc Network (International Journal of Engineering and Computer Science, 2018)
Mobile Ad hoc Network (MANET) is the emerging technology used for various applications such as battlefield communications, emergence operations, search and rescue and disaster relief operations. It consist a group of mobile nodes. The most salient research challenges in this area include end to end data transfer, link access control and security. In order to improve the data transfer between these mobile nodes, many routing protocols are proposed. Opportunistic data forwarding has drawn much attention in the research community of multi hop wireless networking. Opportunistic routing in MANET is a challenging one. Use of efficient routing methods which supports opportunistic routing in MANET will give better throughput with minimum delay and overhead. Here, a tree based proactive source routing called PSR is described that integrates proactive routing and opportunistic data forwarding. It provides low routing overhead and delay without reducing the overall throughput. To maintain source routing, every node keeps a BFST of the entire network rooted at itself. The tree structure is periodically updated by broadcasting these information towards neighbour nodes to keep pro-activity in routing. Routes are updated and unwanted nodes are removed from the tree structure without affecting delay in communication. An efficient tree based PSR is proposed which have the following features. Routing overhead in PSR will be reduced by using streamlined differential update methods. Delay in path identification of PSR can be reduced by using shortest path algorithm. Control packet overhead at higher level nodes can be reduced by using mobile sink node.